'Home away from home': understanding Chinese parents' ideological beliefs and involvement in international school students' language learning. Issue 5 (20th October 2021) - Wan, Zhongyan; Gao, Xuesong (Andy)
ABSTRACT: This longitudinal study draws on family language policy (FLP) research to examine a group of Chinese parents' ideological beliefs, practices, and management efforts related to their children's learning of multiple languages, including Chinese, English, and Spanish in an international boarding school in China. Based on data analysis, including interviews, parents' recorded learning journals, and follow-up observations and discussions, the study revealed that the participants value multilingual competence as a critical resource for access to international education, to maintain alternative identities, and to enable their children to pursue aspirational futures globally. These ideological beliefs underpin their varying practices and management efforts associated with different languages. The data suggest that these parents' FLP is largely influenced by the school curriculum and different layers of contradictions associated with their social, educational, and linguistic realities. The study not only generates insights about the intersections of family and broader contexts (e.g. the international school) in terms of FLP research, it also adds a cultural aspect to understanding FLP processes in the Chinese context.